Thymulin-based gene therapy and pituitary function in animal models of aging - Reggiani, Paula Cecilia (2011)
Thymulin is a thymic hormone exclusively produced by the thymic epithelial cells. After its discovery and initial characterization in the 1970s, it was demonstrated that thymulin production and secretion is strongly influenced by the neuroendocrine system. Conversely, a growing core of information, to be reviewed here, points to thymulin as a hypophysiotropic peptide. Additionally, thymulin was shown to possess anti-inflammatory and analgesic properties in the brain. In recent years, a synthetic DNA sequence coding for a biologically active analog of thymulin, metFTS, was constructed and cloned in different adenoviral vectors. These include bidirectional regulatable Tet-Off vector systems that simultaneously express metFTS and green fluorescent protein and that can be downregulated reversibly by the addition of the antibiotic doxycycline. A number of recent studies suggest that thymulin gene therapy may be a suitable therapeutic strategy to prevent some of the endocrine and reproductive alterations that typically appear in congenitally athymic (nude) mice, taken as a suitable model of neuroendocrine and reproductive aging. The present article briefly reviews the literature on the physiology of the thymulin-pituitary axis as well as on the new molecular tools available to exploit the therapeutic potential of thymulin.